Perceptions and beliefs of adolescent girls regarding adherence to iron supplementation: An analysis using the health belief model - Kamal Agus Efendi; Ari Yuniastuti; Intan Zainafree (KHD-Production, 2025)
Iron deficiency anemia in adolescent girls is a significant public health issue with a high prevalence. Despite the government's launch of the Nutritious Action Program to tackle this problem, its effectiveness is still hindered by low adherence to Iron and Folic Acid (IFA) tablet consumption among adolescents. This qualitative study aims to analyze the factors influencing adherence to IFA tablet consumption in adolescent girls from the Health Belief Model (HBM) perspective. Using a case study design, this research collected data through in-depth interviews with four adolescent girls, one parent, and an expert from IAKMI Kudus. Data analysis was conducted interactively by identifying key themes relevant to the HBM components. The results show that adherence is influenced by the complex interaction of the six HBM components. Adolescents have a good perception of their susceptibility to and the severity of anemia, but this is not enough to overcome the perceived barriers. Physical barriers, such as side effects like nausea, dizziness, and unpleasant taste, are the strongest predictors of non-adherence. Adherence is highly dependent on external cues, such as supervision from teachers and parents, with behavioral differences observed between students living in boarding schools and those who are not. This study concludes that successful interventions must go beyond merely providing IFA tablets. A comprehensive strategy is needed to strengthen adolescents' self-efficacy to overcome barriers and ensure continuous social support from schools and families to achieve sustainable dietary behavior changes.